2012
DOI: 10.2478/v10048-012-0034-5
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Insulated Monopole Sensor Technique for Determination of Moisture Content in Hevea Rubber Latex

Abstract: This paper describes the application of a SMA stub contact panel as an insulated monopole sensor for determination of moisture content in hevea rubber latex. Comparison results between measured and calculated reflection coefficient using King's model are presented. Calibration equations relating moisture content to phase shift have been established in the frequency range from 100 MHz to 5 GHz. The accuracy of the technique was 1.3% when compared to actual moisture content obtained using the gravimetric method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…results obtained indirectly from the dielectric measurements with the actual m.c. found using the microwave oven method (Ansarudin et al 2012).…”
Section: Performance Analysismentioning
confidence: 99%
“…results obtained indirectly from the dielectric measurements with the actual m.c. found using the microwave oven method (Ansarudin et al 2012).…”
Section: Performance Analysismentioning
confidence: 99%
“…With some materials, surface drying tends to form a "skin" that seals the moisture inside, but such effects have not been observed with natural rubber cup lump. In any case, this should not be relevant until relatively high dryness (Liang et al, 2003;Ansarudin et al, 2012). The increased surface area created by slicing the cup lump also reduces the barrier effects of such skin.…”
Section: Moisture Content (Mc) Measurementmentioning
confidence: 99%
“…There are several applications reported that used the microwave technique to sense grain MC, such as a microwave microstrip ring resonator for single wheat grain (Abegaonkar et al, 1999) as well as a prototype moisture meter using a microwave transceiver (Kim et al, 2002), multi-layer microstrip moisture sensor (Jafari et al, 2010) and cylindrical slot antennas for rice grain quality . Besides, microwave technique was also applied in MC determination for oil palm fruit (You et al, 2010a), soybean (Shrestha et al, 2014), tuber (Zainuddin et al, 2013), clay granule (Mextorf et al, 2012), latex (Ansarudin et al, 2012;Mohammadi et al, 2012) and mortar (Jusoh et al, 2011).…”
Section: Introductionmentioning
confidence: 99%